Level of knowledge of Covid-19 among students, teachers and administrative staff belonging to the Facultad de Odontología, Universidad Central del Ecuador - Oña-Toapanta, Ingrid Antonella; Armas-Vega, Ana del Carmen; Cabrera-Arias, Marina Alejandra (Revista Facultad de Odontología Universidad de Antioquia, 2023)
Introduction: Covid-19, a lethal disease that has wreaked havoc worldwide caused a pandemic, affecting almost all aspects of human life, therefore, it is necessary to acquire knowledge about prevention, form positive attitudes and behaviors to avoid more contagions and deaths. The objective was to determine the level of knowledge of Covid-19 among students, teachers and administrative personnel belonging to the Faculty of Dentistry of the Central University of Ecuador. Methods: observational, cross-sectional analytical study, with a sample of 275 participants including dental teachers, administrative personnel, undergraduate and graduate students. Prior to the study, the questionnaire Covid-19 Awareness Among Healthcare Students and Professionals in Mumbai Metropolitan Region: A Questionnaire-Based Survey was translated from English into Spanish, following the due processes of preparation, reconciliation, back-translation and final report. Once the reliability of the questionnaire was established (internal consistency CCI= 0,89 and Cronbach's Alpha α= 0,63), it was applied to the total sample after being designed in Google Forms and sent via e-mail. The data were analyzed in the SPSS v. 26 statistical program using the Chi-Square test. Results: the established average of the median value showed that undergraduate students and professionals with a third level education had a higher level of knowledge than the other groups (p=0,014 and 0,012) respectively. Conclusions: the age group 18-30 years, undergraduate university students and professionals with third level degree had a better level of knowledge about Covid-19.